1987
DOI: 10.1016/s0735-1097(87)80377-7
|View full text |Cite
|
Sign up to set email alerts
|

Progression of hypertrophic cardiomyopathy into a hypokinetic left ventricle: Higher incidence in patients with midventricular obstruction

Abstract: The development of segmental or generalized left ventricular hypokinesia is an unusual occurrence in patients with hypertrophic cardiomyopathy. To determine the incidence and possible pathophysiologic mechanisms responsible for this process, the serial clinical and laboratory data of 62 patients with the diagnosis of hypertrophic cardiomyopathy were analyzed. During a mean follow-up period of 8 years (range 2 to 21), 5 patients (Group A) developed left ventricular hypokinesia, whereas the remaining 57 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(77 citation statements)
references
References 15 publications
1
75
0
1
Order By: Relevance
“…An asynergic or aneurysmal apical chamber in the absence of fixed coronary artery disease has been previously described in a patient with MVO, [8][9][10] and it has been suggested that the development of apical aneurysm may be secondary to increased afterload and high apical pressure resulting from a systolic MVO. 8,10 Therefore, relief of the high apical pressure may be necessary to preventing further asynergy.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An asynergic or aneurysmal apical chamber in the absence of fixed coronary artery disease has been previously described in a patient with MVO, [8][9][10] and it has been suggested that the development of apical aneurysm may be secondary to increased afterload and high apical pressure resulting from a systolic MVO. 8,10 Therefore, relief of the high apical pressure may be necessary to preventing further asynergy.…”
Section: Discussionmentioning
confidence: 90%
“…8,10 Therefore, relief of the high apical pressure may be necessary to preventing further asynergy. It has been considered that drug-refractory patients with MVO are candidates for cardiac surgery, 11,12 but recently, pacing therapy for pressure gradient reduction in patients with MVO has been reported, 6 as is the case for patients with hypertrophic LVOT obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The dyskinetic/akinetic apical aneurysm can provide the structural basis for intracavitary thrombus formation. 6 Other possible cause of LV aneurysm include post myocardial infarction. Our patient had no history of angina or myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Fighali et al showed that segmental or generalized left ventricular hypokinesis could develop in patients with HCM and midventricular obliteration without a fixed coronary artery obstruction, 7 and they speculated that a possible cause of such hypokinesis was that the large pressure gradient at the midventricular level might lead to further compensatory apical hypertrophy, which could in turn make the flow obstruction more severe and the pressure in the apical chamber higher. The pressure overload on the apical wall might eventually lead to myocardial dysfunction with dilation of the apical chamber.…”
Section: Discussionmentioning
confidence: 99%